Degree of the residual alveolar ridge resorption registrated by ortopantomograms among immediate and classic complete denture users - Marković Dubravka; Krstić Mirjana 1; Đurić Milanko; Brkanić Tatjana (Serbian Medical Society - Dental Section, Belgrade, 2002)
Degree of residual ridge loss is influenced by sistemic phactors, but during the first phase after extraction local phactors are dominant. Patohistological changes of alveolar processus of jaws show the possibility of negative influence of complete dentures on support tissue. In this study, on the chosen sample, the degree of alveolar ridge loss was measured in the group of immediate complete denture users (30 patients) and classical complete denture users ( 30 patients).Height of residual alveolar ridge was measured on ortopantomograms. Localization of referent points proportion was used because of neutralization of shadow distorsion (five in maxilla and five in mandibula). The first ortopantomogram was made at the time of delivering dentures, and the second one six months later. The final measurement of alveolar ridge height is bigger in the group with classical dentures. The reduction degree of residual alveolar ridge is bigger in the group of immediate complete denture users in the first six months.